Tracking of marine predators to protect Southern Ocean ecosystems - Hindell, Mark A.; Reisinger, Ryan R.; Ropert-Coudert, Yan; Hückstädt, Luis A.; Trathan, Philip N.; Bornemann, Horst; Charrassin, Jean-Benoît; Chown, Steven L.; Costa, Daniel P.; Danis, Bruno; Lea, Mary-Anne; Thompson, David; et al. (Nature (London), 2020)
Southern Ocean ecosystems are under pressure from resource exploitation and climate change 1 , 2 . Mitigation requires the identification and protection of Areas of Ecological Significance (AESs), which have so far not been determined at the ocean-basin scale. Here, using assemblage-level tracking of marine predators, we identify AESs for this globally important region and assess current threats and protection levels. Integration of more than 4,000 tracks from 17 bird and mammal species reveals AESs around sub-Antarctic islands in the Atlantic and Indian Oceans and over the Antarctic continental shelf. Fishing pressure is disproportionately concentrated inside AESs, and climate change over the next century is predicted to impose pressure on these areas, particularly around the Antarctic continent. At present, 7.1% of the ocean south of 40°S is under formal protection, including 29% of the total AESs. The establishment and regular revision of networks of protection that encompass AESs are needed to provide long-term mitigation of growing pressures on Southern Ocean ecosystems. Tracking data from 17 marine predator species in the Southern Ocean are used to identify Areas of Ecological Significance, the protection of which could help to mitigate increasing pressures on Southern Ocean ecosystems.